Pandangan Islam Dalam Memaknai Hakikat Manusia - Aryandika Firmansyah; M. Yazid Fathoni; Wismanto Wismanto; Dio Herfanda Bangun; Muhammad Hanif Nasution (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The mysteries of humanity are like the mysteries of nature: the more dimensions we know, the more we realize that there are still many unknown things. Humans are a symbol of the natural wonders created by God. There are people who have very attractive personalities and it is from their strong and noble personalities that they achieve success in society, become honorable people and are respected by society. Quraish Syihab in his book "The Science of the Qur'an" expresses Alexis Carrel's views regarding the difficulties faced in understanding human nature, according to which "humans have essentially devoted enormous attention and effort to understanding ourselves, even when we has quite a large nature. This research uses qualitative methods with a library research approach. The results of this research show that the nature of humans in the Islamic view is that humans were created to worship Allah Subhanahu Wa Taala, and the indicator of those who are said to believe and be devoted to Allah Subhanahu Wa Taala is that they believe in Allah Subhanahu Wa Taala, then they are patient in all forms. tests that Allah gives and be grateful if you are given favors, then advise each other on the truth.